Fraud dalam Perspektif Islam - Safuan Safuan; Budiandru Budiandru; Ismartaya Ismartaya (Owner : Riset dan Jurnal Akuntansi, 2021)
Islam regulates all the problems of its people, one of which is regulated by Islam, namely the relationship between humans. This study aims to try to reveal how cheating or cheating behavior is from an Islamic perspective. The investigation technique used in this study is a qualitative method with a literature review approach where the researcher collects some literature from both international and national journals. The data taken from these journals are then used as study material in writing this research. The results of the study illustrate that Islam has provided clues or signs of cheating or fraudulent behavior through the Koran and Hadith. From the results of the study, it is known that Islam has regulated all the problems of its people, especially the problem of fraud, Islam forbids its followers to do this. In addition, this research reveals that the practice of deception or what is known as cheating has existed for centuries, and Islam has clearly and emphatically provided a picture of how fraud occurs and how the impact of punishment on its followers. This research is also expected to contribute to knowledge related to fraud or fraudulent practices as well as a contribution to enlightenment for society.